Extreme prematurity and perinatal management. (19th April 2018) - David, Anna L; Soe, Aung
Abstract : Key content: Perinatal management of pregnant women delivering at the threshold of viability has medical and ethical considerations. It should be preceded by the best advice from a multidisciplinary neonatal and obstetric team to fully inform parents and achieve a consensus on the optimal care for the mother and neonate. Obstetric interventions can affect maternal and neonatal outcomes after birth at the threshold of viability. These include administration of steroids, magnesium sulphate and tocolysis, fetal monitoring in labour and mode of delivery. Obstetric complications such as malpresentation are common and can affect delivery choices at extreme preterm gestational ages. This requires obstetricians to plan carefully with parents before labour starts. Learning objectives: To understand how obstetric decisions and interventions can affect maternal and neonatal outcomes when women are at risk of delivery at extreme premature gestational ages. To enable trainee obstetricians to better counsel women and their partners about possible complications before and during labour at extreme preterm gestations. Ethical issues: Should we monitor the fetal heart during labour, deliver by caesarean section and resuscitate a baby born at extreme prematurity when short‐term and long‐term neonatal outcomes are likely to be poor?